Cutting temperature prediction in negative-rake-angle machining with chamfered insert based on a modified slip-line field model. (1st February 2020) - Hu, Cheng; Zhuang, Kejia; Weng, Jian; Zhang, Xiaoming; Ding, Han
Highlights: A novel slip-line field model concerning DMZ formation in negative-rake-angle machining with chamfered insert is proposed. An analytical approach to temperature prediction considering multiple heat sources and non-uniform heat partition is developed. The material flow states adjacent to DMZ, local shear flow stresses and associated heat generation issues in PDZ, SDZ and DMZ are determined and described in detail. Validations exploiting various FE simulations and orthogonal cutting trials of AISI 304 stainless steel with chamfered inserts are carried out. Abstract: Chamfered inserts have shown superior edge resistance and prolonged tool life in practical machining process. However, such kind of inserts find limited application in metal cutting due to the inadequate understanding of their sophisticated influences on cutting performance. Researches on material flow mechanism and heat generation issues in the vicinity of the chamfer may contribute to the comprehensive cognition of high-performance cutting with chamfered inserts. In this paper, a novel slip-line field model has been developed for negative-rake-angle machining with chamfered insert. The slip-line field geometry concerning dead metal zone (DMZ) formation is demonstrated utilizing the slip-line approach. Moreover, an iterative methodology is developed to determine local shear flow stresses, interface frictional factors and heat sources intensity. Then, analytical modeling of temperature fields in tool and workpiece is carried out by employing classical orthogonal cutting theory and semi-boundary heat transfer principles. Finally, two main approaches including two-dimensional (2-D) finite-element (FE) simulations and orthogonal cutting trials of AISI 304 stainless steel are adopted for verification. Simulated slip-line field geometry with respect to DMZ and involved angles are extracted to compare against the predictions from the proposed slip-line solution. The simulated and measured temperature fields are compared with the predicted results from the developed thermal model. In addition, a contrastive model from previous literature is also compared with the proposed model. Encouraging agreements have been detected between those comparisons, which indicate the reasonableness and reliability of the given analytical model. The result reveals that the presented model gives much better prediction of temperature distribution upon chamfer insert over the contrastive model, especially at the DMZ-tool interface. Graphical abstract: Image, graphical abstract